Colorectal cancer screening in Lynch syndrome: Indication, techniques and future perspectives. Issue 4 (27th May 2020) - Perrod, Guillaume; Rahmi, Gabriel; Cellier, Christophe
Abstract : Lynch syndrome (LS) is an inherited predisposition to colorectal cancer (CRC), responsible for 3–5% of all CRC. This syndrome is characterized by the early occurrence of colorectal neoplastic lesions, with variable incidences depending on the type of pathogenic variants in MMR genes ( MLH1, MSH2, MSH6, PMS2 and EPCAM ) and demographics factors such as gender, body mass index, tobacco use and physical activity. Similar to sporadic cancers, colorectal screening by colonoscopy is efficient because it is associated with a reduction >50% of both CRC incidence and CRC related mortality. To that end, most guidelines recommend high definition screening colonoscopies in dedicated centers, starting at the age of 20–25 years old, with a surveillance interval of 1–2 years. In this review, we discuss the importance of high definition colonoscopies, including the compliance to specific key performance indicators, as well as the expected benefits of specific imaging modalities including virtual chromoendoscopy and dye‐spray chromoendoscopy.